Aboriginal health and the mainstream news media - Leach, V.; James, R.; McManus, Alexandra; Thompson, S. (Health communication resources limited, 2013)
To guide journalists as they navigate the Aboriginal health sector in the course of news gathering and reportage, consists of advice given by participating Aboriginal health professionals to journalists.